E-Government and transformation of service delivery in Malaysia - Siddiquee, Noore Alam; Mohamed, Mohd Zin (IGI Global, 2015)

(untitled)
Since the 1990s e-government has been a leading feature of public sector reform in Malaysia. As elsewhere around the world, at the core Malaysia’s e-government agenda is the desire to reinvent governance and service delivery so as to realize national developmental goals. Variety of e-initiatives undertaken and implemented over the past decades has improved the nation’s e-profile and readiness. These programs have also brought about profound changes to the mode of service delivery and the nature of interactions between the government and citizens and other stakeholders. The paper demonstrates the current trends in e-government by focusing on some most recent initiatives and their roles in modifying governance and service delivery systems thereby producing benefits of efficiency, improved access and convenience, among others. It argues that while Malaysia has made significant inroads in e-services and is ahead of most developing countries, yet progress remains unsatisfactory when compared with regional and world leaders. The paper sheds lights on current impediments of e-government in Malaysia and their implications.